Dynamic covalent Schiff-base silicone polymers and elastomers. (3rd January 2019) - Bui, Robert; Brook, Michael A.
Abstract: Polymers with dynamically exchanging crosslinks possess the ability to be repurposed, in whole or part, following a stimulus. The ability of imines to undergo dynamic exchange reactions under mild conditions was utilized to chain extend or crosslink silicone polymers. Schiff-base crosslinked polysiloxanes were prepared by reacting aminopropyl-functionalized polydimethylsiloxane with aromatic aldehydes. The reactions occur efficiently and the water byproduct spontaneously separates from the silicone if the weight fraction of silicone is sufficiently high. The physical properties of the products were readily tunable by crosslink density; the most practical reaction partners were commercial pendant aminopropylsilicones with terephthaldehyde, although telechelic silicones and triformylbenzene were also utilized. Complete breakdown of the polymers occurred with addition of excess amine. Silicone imine cleavage with excess aldehyde also occurred, but the two processes followed different pathways. The rate of the dynamic processes was increased with good solvents, or acid or amine catalysts. However, even in the absence of catalysts the dynamic transimination was efficient. Simply placing two strips of the elastomer in contact led to an adhesive bond that, depending on contact surface area, was stronger than the cohesive strength of the rubber. The process of self-healing was followed using rheology and was shown to be complete within an hour. Surface modification of elastomers with amines occurred in water, or at aminated solid surfaces. Graphical abstract: Highlights: Aromatic imines rapidly form under mild conditions from aminopropylsilicones. Polyimines are thermally stable and stable to moisture. The polyimines exhibit a chemoplastic behavior via dynamic bond exchange in the presence of amines or acid catalysts. Strong adhesion and self-healing are exhibited by these polymers.